The Effectiveness of Sargassum sp as Liquid Organic Fertilizer in Increasing The Growth of Red Chillies - Yusnaeni; Nikmah; Maryanto C. Honin; Dionisius Bako (Indonesian Journal of Science and Education, 2022)
This study aims to determine the effect of the most effective volume of watering for Sargassum sp liquid organic fertilizer on the growth of red chili plants. The study was an experimental study using a completely randomized design with 5 treatments of watering volume of Sargassum sp liquid organic fertilizer, namely 0 mL (control), 50 mL, 100 mL, 150 mL, and 200 mL. Each treatment was repeated 4 times. The variables measured were plant height, number of leaves, and number of branches. Observational data were analyzed using analysis of variance and further tested by BNT. The results of the analysis of variance showed that the organic fertilizer treatment of Sargassum sp. very significant effect on the variables of plant height, number of leaves, and number of branches, where each variable shows the value of Fcount > Ftable. Further test results showed that the best treatment was Sargassum sp treatment with a watering volume of 200 mL/polybag.